The GPS for thinking: How AI partners are reshaping student metacognition - Sayed Mahbub Hasan Amiri; Naznin Akter; Marzana Mithila; Md. Mainul Islam (CV. Literasi Indonesia, 2026)
Generative artificial intelligence is rapidly becoming a cognitive partner in education, capable of planning tasks, monitoring progress, and evaluating solutions on a learner’s behalf. This conceptual synthesis paper examines the risk that such AI tools, while improving immediate performance, may erode students’ metacognitive abilities in their capacity to plan, monitor, and evaluate their own thinking. Drawing a parallel with GPS navigation research, where habitual turn-by- turn guidance has been shown to impair spatial memory and hippocampal engagement, we introduce the metaphor of AI as a “GPS for thinking